STUDI PRAKTIK PENGGUNAAN PESTISIDA DAN KEJADIAN ANEMIA PADA PETANI BUAH DI DESA TUNGGAK KECAMATAN TOROH KABUPATEN GROBOGAN - Rizqiana Fauziyyah; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Tunggak is one of the fruit-producing areas in which the use of pesticides is still finding of a wide variety of pesticides and that most farmers have not yet used a complete Personal Protection Equipment. Besides, the Puskesmas (Public Health Center) have not examined the hemoglobin levels so that it has not been known whether they have anemia. The purpose of this research is to understand the practice of pesticide use and the anemia cases happened to fruit farmers. The research was conducted in Tunggak Village, Toroh Subdistrict, Grobogan District. It was done with quantitative approach and by using Cross Sectional study design. There were 37 respondents taken as samples. The data was processed by using Rank Spearman and Chi-square statistical test. The result showed 34,8% of knowledge is not good, 52,2% APD did snot complete, 52,2% dose of pesticide do not match, 69,6% amount of oesticides > 3 types, 87% the frequency of spraying is often 73,9% farmers working last long.The results of the examination of farmers’ hemoglobin level showed that 8.7% of them suffers from anemia. In conclusion, there is no correlation between knowledge (p-Value = 0,949), completeness of APD (p-Value = 0,742), pesticide density (p-Value = 0,156), pesticide (p-Value = 0,529) Frequency of spraying (p-Value = 0,104) and length of service (p-Value = 0,194) with anemia cases on fruit farmers in Tunggak, Toroh, Grobogan.